Investigation of Environmental Related Course Gains at the First Level of Primary Education in Terms of Interdisciplinary Approach - YURTTAŞ, Arefe; ERDAŞ KARTAL, Eda; ÇAĞLAR, Atila (Kastamonu Egitim Dergisi, 2021)
Purpose: Environment is an interdisciplinary research field related to many social, cultural, psychological, economic and social fields. Therefore, the success of a study to be planned in environmental education requires directing the study by considering these disciplines. Since environment and environmental problems affect many areas in our lives, environmental education in education programs should be handled with an interdisciplinary approach. In the research, environmental related gains in primary education curriculum were examined in the context of associating with other disciplines based on integrated interdisciplinary approach.Design/Methodology/Approach: The study is qualitative research and document analysis method was used in the analysis of the data.Findings: The number of environmental related gains at primary level was determined to be 96. It has been determined that the environmental related gains in primary education curriculum are concentrated in some courses such as Life Science, Science and Social Studies, and these gains are not included in the curriculum of some courses. It has been observed that the level of association of the determined gains with other disciplines is weak. In addition, no clear explanation has been found in the curriculum about the necessity of handling environmental related gains with an interdisciplinary approach.Highlights: The research shows that environmental gains in primary education curriculum are insufficient in terms of integrated interdisciplinary approach.
Keywords: 13. Climate action; 4. Education